2016
DOI: 10.1140/epjb/e2016-60639-0
|View full text |Cite
|
Sign up to set email alerts
|

Asymmetry through time dependency

Abstract: Abstract. Given a single network of interactions, asymmetry arises when the links are directed. For example, if protein A upregulates protein B and protein B upregulates protein C, then (in the absence of any further relationships between them) A may affect C but not vice versa. This type of imbalance is reflected in the associated adjacency matrix, which will lack symmetry. A different type of imbalance can arise when interactions appear and disappear over time. If A meets B today and B meets C tomorrow, then… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2016
2016
2017
2017

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 25 publications
1
3
0
Order By: Relevance
“…We note that these conclusions are consistent with the results in [28], where an algorithm was proposed to quantify the asymmetry caused by the arrow of time. Our computations also make it clear that, in the Katz setting, use of the supra-centrality matrix also requires a third parameter to be chosen, for the resolvent system involving M.…”
Section: New Block Formulation Vs Supra-centrality Matrixsupporting
confidence: 91%
“…We note that these conclusions are consistent with the results in [28], where an algorithm was proposed to quantify the asymmetry caused by the arrow of time. Our computations also make it clear that, in the Katz setting, use of the supra-centrality matrix also requires a third parameter to be chosen, for the resolvent system involving M.…”
Section: New Block Formulation Vs Supra-centrality Matrixsupporting
confidence: 91%
“…This first example describes a call made the day 1 by the caller #349 to the receiver #23 at a time between 00:00 and 00:59 with a duration of 1634 milliseconds. [38], communication network anomaly detection [39], tracking based on call log analysis [30,31], interactive visual analytics [40], and so on. In this research, the VAST data set has been chosen because it has been used widely in this field and, in our case, the extraction of calling patterns is proposed solely from CDR data.…”
Section: Original Datasetmentioning
confidence: 99%
“…In ( Taylor et al 2017 ) a block-matrix approach was suggested which allows centrality measures for static networks to be applied. However, as mentioned in ( Mantzaris and Higham 2016 ), that formulation does not fully respect the arrow of time.…”
Section: Introductionmentioning
confidence: 98%
“…In a case study on Twitter data, this approach was seen to be successful, in the sense of correlating well with the independent views of social media experts (Lafin et al 2013 ). It was also found to outperform the crude alternative of simply aggregating all edges into a single static network that forgets the time-ordering of the interactions; see ( Mantzaris and Higham 2016 ) for further discussion. Tests in (Chen et al 2016 ; Mantaris and Higham 2013 ) also showed that dynamic broadcast centrality can be effective at quantifying the potential for the spread of disease across time-ordered interactions.…”
Section: Introductionmentioning
confidence: 99%